Czym może się stać postanalityczna filozofia prawa? - Paździora, Michał (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The article contains reflections on the understanding of postanalytic philosophy and, subsequently, the postanalytic philosophy of law. It presents an overview of the positions in this regard and the reconstruction of essential arguments put forward by postanalytic philosophers against the analytic tradition. In particular, it focuses on the criticism of the adoption of scientific method in legal knowledge and possibility of the “external point of view” on the study of language.
Keywords: introduction